Development of virtual reality math media in the junior high school Indonesia-Malaysia with group investigation model - Buchori, Achmad; Osman, Sharifah (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
Conventional mathematics learning is felt to be less interesting and boring for students. Students need innovative learning and make students active in learning. To improve students' understanding of learning mathematics, innovation is needed in innovative learning media. This study aims to produce a product in the form of virtual reality media in mathematics learning based on the group investigation model. This study uses the ADDIE research method with analysis, design, development, implementation, and evaluation stages. Before being tested, the media was validated by a media expert validator with a result of 86% in the